Pendampingan Kegiatan Santri Ponrdok Pusat Pesantren Zainul Hasan Genggong Guna Menjadikan Santri Produktif Dan Inovatif - Wardatul Magfiroh, Siti; Syarifah , Ifadatus; Muzaqiyah , Nurul (Najah: Journal of Research and Community Service, 2024)
Islam is a universal religion, therefore Islam must be spread to all mankind through its easy-to-implement Shari'a. Thus, human beings are not only obliged to carry out the teachings of Islam in their daily lives, but they also have to convey or preach the truth of Islamic teachings to others. Islamic boarding schools as one of the existing institutions in society have a very important role in improving the quality of human resources. One of them is to improve the spiritual abilities of students in Islamic boarding schools, namely UBUDIYAH training which is emphasized on each student as a booster for Islamic education in improving the quality of religion for each individual and in society later. In dealing with these conditions, Islamic boarding schools, in this case as Islamic institutions, are required to appear as one of the most important elements in order to produce generations of students who are professional in the fields of religion and education. With the embodiment through UBUDIYAH activities using effective and efficient methods and teaching.